2001
DOI: 10.4314/wsa.v27i3.4973
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological modelling of fine sediments in the Odzi River, Zimbabwe

Abstract: Siltation of reservoirs is a major concern in Zimbabwe. Therefore, development of prediction tools is of great importance. In the present study a recently developed empirical sediment model (HBV-SED) based on a daily rainfall-runoff model was applied to simulate riverine fine sediment transport in a 2 486 km 2 catchment in eastern Zimbabwe. The model performance was evaluated and changes in the model structure were suggested. The modelling was, however, associated with many uncertainties due to the adopted sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Pan evaporation (cumulated to monthly time step from available daily values) from HCB for the same time period was used, and was multiplied by a factor of 0.8 so that it closely reflected plant water use (Lidén et al 2001;Gumindoga et al 2016). The average monthly evaporation rates as required in the model were calculated from the daily pan evaporation obtained.…”
Section: Meteorological Inputs Into Hec-hms Modelmentioning
confidence: 99%
“…Pan evaporation (cumulated to monthly time step from available daily values) from HCB for the same time period was used, and was multiplied by a factor of 0.8 so that it closely reflected plant water use (Lidén et al 2001;Gumindoga et al 2016). The average monthly evaporation rates as required in the model were calculated from the daily pan evaporation obtained.…”
Section: Meteorological Inputs Into Hec-hms Modelmentioning
confidence: 99%
“…In the context of sediment flux modelling, Lidén et al (2001) tested the HBV-SED model on a basin in Zimbabwe. The hydrological component of the model was calibrated using 1-to 5-year periods.…”
Section: Sensitivity Analysis Of Rainfall-runoff Models To the Amountmentioning
confidence: 99%
“…Population density of whole catchment is above 60 persons per km 2 in large parts of the catchment; land use is a mixture of communal lands, commercial farms and forests [30]. On the commercial areas, large farms are found, which run extensive farming.…”
Section: Demography and Land Usementioning
confidence: 99%
“…It is a perennial river that rises in the Eastern Highlands and flows to the south before feeding the Save River. Total catchment area is 2486 km 2 ; altitude difference is large, 950 to 2160 m a.s.l [30]. However this study shall focus on the upper sections of the sub catchment, as shown in Figure Figure 2 hereafter termed micro catchment.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation